2016
DOI: 10.1186/s12885-015-2045-8
|View full text |Cite
|
Sign up to set email alerts
|

Successful en bloc venous resection with reconstruction and subsequent radiotherapy for 2 consecutive recurrences of intravenous leiomyoma—a case report

Abstract: BackgroundIntravenous leiomyomas are a rare variant of uterine leiomyoma. Although histologically benign, these tumors are associated with a poor prognosis due to propensity for metastasis, high recurrence rate, difficulty of obtaining complete resection, and frequent extension into and along major veins.Case presentationWe describe a 43-year-old patient initially presenting with lower abdominal pain. Clinical examination revealed a large right pelvic mass that was shown by computed tomography (CT) to surround… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…A case with increase of tumor burden was described after Tamoxifen treatment emphasizing the necessity to consider carefully the indication of hormonal therapy [59] . Radiotherapy at low doses is described in patients at high risk of recurrence [60] .…”
Section: Discussionmentioning
confidence: 99%
“…A case with increase of tumor burden was described after Tamoxifen treatment emphasizing the necessity to consider carefully the indication of hormonal therapy [59] . Radiotherapy at low doses is described in patients at high risk of recurrence [60] .…”
Section: Discussionmentioning
confidence: 99%
“…10) Its clinical manifestation shows progression to involve the iliac veins, the inferior vena cava, and even the right atrium. 11) A complete history taking can provide clues. Pathologically, this tumor contains endothelial cells that can be positive for CD31, CD34, vimentin, and smooth muscle actin.…”
Section: Discussionmentioning
confidence: 99%
“…Pathologically, this tumor contains endothelial cells that can be positive for CD31, CD34, vimentin, and smooth muscle actin. 11)…”
Section: Discussionmentioning
confidence: 99%
“…Smooth muscle tumors may increase in size with local invasion to the mediastinum and other structures, which can jeopardize complete resection with curative intent. If further surgery is contraindicated and disease was left behind perhaps the role of radiation could be explored [ 17 20 ]. Al-Daraji et al [ 7 ] reported a case where there was a concern for possible incomplete resection at the apex and this patient received radiation with the intention to reduce the risk of local recurrence.…”
Section: Discussionmentioning
confidence: 99%